Current status and future directions of anti-angiogenic therapy for gliomas - Wick, Wolfgang; Platten, Michael; Wick, Antje; Berberich, Anne; Radbruch, Alexander; Bendszus, Martin; Winkler, Frank (Neuro-Oncology, 2016)
Abstract. Molecular targets for the pathological vasculature are the vascular endothelial growth factor (VEGF)/VEGF receptor axis, integrins, angiopoietins, an
Advance Access date 12 October 2015
Gesehen am 11.03.2020